1997
DOI: 10.1046/j.1469-7580.1997.19040505.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibre size and type distribution in thoracic and lumbar regions of erector spinae in healthy subjects without low back pain: normal values and sex differences

Abstract: This study sought to investigate the normal muscle fibre size and type distribution of the human erector spinae, both in thoracic and lumbar regions, in a group of 31 young healthy male (n = 17) and female (n = 14) volunteers. Two percutaneous muscle biopsy samples were obtained under local anaesthesia, from the belly of the left erector spinae, at the levels of the 10th thoracic and 3rd lumbar vertebrae. Samples were prepared for routine histochemistry for the identification of fibre types. Fibre size (cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
6
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(167 citation statements)
references
References 39 publications
10
139
6
5
Order By: Relevance
“…Les femmes possèdent-elles un niveau d'endurance plus élevé que celui des hommes et pour quelles tâches (Speechly, Taylor et Rogers 1996 ;Mannion et autres 1997) ? Jusqu'où les hommes dépassent-ils leurs limites physiques en surestimant leur capacité à lever des poids (Mitai 1984) ?…”
Section: La Condition Physique Et Les Tests De Sélectionunclassified
“…Les femmes possèdent-elles un niveau d'endurance plus élevé que celui des hommes et pour quelles tâches (Speechly, Taylor et Rogers 1996 ;Mannion et autres 1997) ? Jusqu'où les hommes dépassent-ils leurs limites physiques en surestimant leur capacité à lever des poids (Mitai 1984) ?…”
Section: La Condition Physique Et Les Tests De Sélectionunclassified
“…Assim, durante um levantamento repetitivo, os músculos da coluna fadigada tornam-se menos efetivos na geração de um momento extensor essencial requerido, possibilitando um estresse relativo aos discos intervertebrais e ligamentos e tornando, portanto, as estruturas da coluna susceptíveis à lesão e/ou à dor (MANNION, 1999). Além do mais, a fadiga da musculatura da coluna é acompanhada por uma diminuição do controle do movimento do tronco, por uma alteração na coordenação das atividades musculares e pela perda da estabilidade do tronco (PARNIANPOUR et al, 1988;KENDALL;McCREARY;PROVANCE, 1995 Cabe ressaltar que, segundo Mannion, et al (1997), Mannion, et al (1998), Mannion (1999 e Demoulin et al (2006), o processo de fadiga muscular, notadamente da musculatura extensora da coluna, é diferente entre homens e mulheres, e esta diferença está relacionada a uma variação da morfologia dos tecidos lombares em relação à proporção das fibras tipo 1 e tipo 2 para homens e mulheres. Clark et al (2003) também encontraram em seu estudo diferenças entre homens e mulheres em relação à fadiga da musculatura extensora da coluna lombar, porém para esses autores as diferenças são explicadas devido ao tipo de contração muscular e à quantidade de força gerada.…”
Section: Introductionunclassified
“…De acordo com Mannion et al (1997), Mannion et al (1998) (BORK et al, 1996;SHIMABUKURO et al, 2012). O referido instrumento pode ser um indicativo para comparar a situação encontrada antes e após uma intervenção ergonômica.…”
Section: Introductionunclassified
“…Our previous study results indicated that the measurement of back muscle fatigability, especially the erector spinae muscle, indicated that the entropy analysis was a more reliable measure than the power spectral analysis (Sung et al, 2008b). It is well known that the observed EMG signal depends on anatomical factors, such as muscle geometry, subcutaneous fat, gender, and other confounding factors (Lindstrom et al, 1974;Mannion et al, 1997c;Pullman et al, 2000;Roy et al, 1997;Solomonow et al, 1990). As a result, observed quantities from EMG signals show considerable variations even among a group of healthy subjects.…”
Section: Reliability Of Surface Electromyography Analysismentioning
confidence: 99%
“…The myoelectric signals are the instantaneous algebraic summation of all electrical discharges produced by a contraction of the muscle fibers. Muscle fatigue is quantified using surface EMG signals based on the power spectrum which is the Fourier transform of EMG time series (Knowlton et al, 1951;Mannion & Dolan, 1994;Mannion et al, 1997c). Normal electrical source is a muscle membrane potential of approximately -90 mV, and measured EMG potentials range between less than 50 μV and up to 20 to 30 mV, depending on the muscle under observation (Herzog et al, 1987;Nigg et al, 1988).…”
Section: Introductionmentioning
confidence: 99%